Effect of Plyometric Exercises of Lower Limb on Strength, Postural Control, and Risk of Falling in Stroke Patients - Abd Elsabour, Ahmed K.; Zakaria, Hoda M.; Fahmy, Ebtesam M.; Khalil, Azza Sayed Abdelrehim; Alwhaibi, Reem M.; Ragab, Walaa M.; Taha, Shreen I. (Medicina (Kaunas, Lithuania), 2025)
Background and Objective: Stroke, a major contributor to long-term disability worldwide, often results in significant impairments in motor function. These impairments can include weakness, impaired balance, and decreased coordination, which can have a significant influence on one’s quality of life and independence. Finding an effective protocol for rehabilitation to improve these points will decrease the impact of stroke and its coast of rehabilitation. Materials and Methods: This study was conducted to assess the effect of lower limb plyometric exercises on strength, postural control, and risk of falling in stroke patients. Materials and Methods: This study involved 40 chronic left stroke patients randomly divided into two equal groups. The experimental group participated in a 12-week supervised plyometric training program, while the control group received conventional physical therapy program. Lower limb muscle strength was measured using a handheld dynamometer, and balance and fall risk were assessed via the Biodex Balance System (BBS). These measurements were conducted before and after the intervention period to evaluate treatment effects. Results: The results of this study demonstrated significant improvements in muscle strength and balance parameters among stroke patients who underwent plyometric exercise compared to those receiving a conventional program. The plyometric group exhibited significantly greater increases in knee extension strength (p < 0.05), hip abduction strength (p < 0.05), ankle dorsiflexion strength (p < 0.05), and ankle eversion strength (p < 0.05). Furthermore, the plyometric group showed significant improvements in overall stability (p < 0.05), mediolateral stability (p < 0.05), and anteroposterior stability (p < 0.05), as measured by the Biodex Balance System (BBS). Conclusions: The results of this study suggest that plyometric exercise may be an effective intervention for decreased risk of falling and enhancing muscle strength and balance during recovery from stroke.